Remarks on X‐ray constrained/restrained wavefunction fitting. Issue 3 (26th May 2022) - Bürgi, Hans-Beat; Genoni, Alessandro
Abstract : Some comments concerning the meaning and significance of X‐ray constrained/restrained wavefunctions are given. Abstract : X‐ray constrained/restrained wavefunctions (XCWs/XRWs) result from a combination of theory and experiment and are therefore affected by experimental errors and model uncertainties. The present XCW/XRW procedure does not take this into account, thus limiting the meaning and significance of the obtained wavefunctions.